Asymmetric α-amination of 3-substituted oxindoles using chiral bifunctional phosphine catalysts - Jin, Qiao-Wen; Chai, Zhuo; Huang, You-Ming; Zou, Gang; Zhao, Gang (Beilstein Journal of Organic Chemistry, 2016)
A highly enantioselective α-amination of 3-substituted oxindoles with azodicarboxylates catalyzed by amino acids-derived chiral phosphine catalysts is reported. The corresponding products containing a tetrasubstituted carbon center attached to a nitrogen atom at the C-3 position of the oxindole were obtained in high yields and with up to 98% ee.
Keywords: 3-aminooxindoles; asymmetric catalysis; phosphine catalyst; tetrasubstituted stereogenic carbon centers